A monoclonal antibody against human complement component C3: the production of C3 by human cells in vitro. - Whitehead, A; Sim, R; Bodmer, W (1981)
A monoclonal antibody (WM1) against the third component of human complement (C3) was produced by fusing P3-X63-Ag8 mouse myeloma cells with spleen cells from BALB/c mice immunized with purified C3. The specificity of WM1 antibody against C3 was established by its capacity to inhibit a standard C3 hemolytic assay and to immunoprecipitate C3 from human serum in the presence of S. aureus bacteria. Indirect binding assays indicate that the antibody is directed the C3c portion of C3. The immunoprecipitation technique was used to screen for the presence of C3 in the culture supernatants of various cell lines. By this means, C3 was identified as a secreted product of human primary fibroblasts, transformed fibroblasts and D98/AH-2, a HeLa derivative, but not of other human cell lines. WM1 was unable to immunoprecipitate C3 from rabbit or mouse fibroblast culture supernatants.